Pencegahan Stunting pada Balita melalui Upaya Penerapan Enam Prinsip Higiene Sanitasi Pangan Rumah Tangga: Prevention Stunting for Child Under Five Years Old through Implementation Efforts of Six Principles of Food Higiene Sanitatin on Household - Gunawan, Asep Tata; Nuryanto, Nuryanto; Lukmitarani, Ratih; Utomo, Budi; Widiastuti, Anita (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Consuming food contaminated with physical, chemical, and bacteriological substances can cause diarrhea and worms, which results in children under five years old experiencing lacking nutrition and growth disorders, putting them at risk of stunting. The six principles of food sanitation hygiene aim to reduce the risk of disease transmission and health problems from consuming food. These community empowerment activities aim to increase the knowledge of health cadres in preventing stunting for children under five years old through implementation efforts of six principles of food hygiene sanitation in households. The target of this activity was 47 health cadres. Activity stages include coordination, preparation of pocketbooks, training, and evaluation. Statistical analysis was conducted for differences in health cadres' knowledge levels before and after training using the dependent t-test. The results of the coordination show that there is support and participation from 3 built villages, including Pandak, Karangmangu, and Kemutug Kidul villages. Arranged a pocketbook on stunting prevention and six principles of food sanitation hygiene as a reference for health cadres for outreach to the community. The training showed increased health cadres' knowledge before and after the activity (p-value=0.001). The results of community empowerment can be used as input for policymakers at the Baturraden II Primary Health Center and the District Health Officer Banyumas to accelerate stunting reduction through counseling on six principle hygiene sanitation implementation in households in sustainable.